General System of Royalties in Colombia 2012 2014 (2015)
From the Legislative Act 05 of 2011, "with which the General System of Royalties will be created and Articles 360 and 361 of the Constitution of Colombia of 1991 were modified" and the Law 1530 of 2012, a description of the regulation is made, structure, operation, bodies and distribution of established resources for this system, then an analysis of results obtained from its implementation until 2014 to determine if after three years of applying the principles with which this reform was based are met it is made : Saving, Equity, Regional Competitiveness and governance; and finally to reflect on the aspects to consider looking for an efficient and effective use of resources from royalties, which materializes in economic, social, technological and environmental development in all regions of the country.